Osteoporosis and autophagy: What is the relationship? - Florencio-Silva,Rinaldo (2017)
Summary Autophagy is a survival pathway wherein non-functional proteins and organelles are degraded in lysosomes for recycling and energy production. Therefore, autophagy is fundamental for the maintenance of cell viability, acting as a quality control process that prevents the accumulation of unnecessary structures and oxidative stress. Increasing evidence has shown that autophagy dysfunction is related to several pathologies including neurodegenerative diseases and cancer. Moreover, recent studies have shown that autophagy plays an important role for the maintenance of bone homeostasis. For instance, in vitro and animal and human studies indicate that autophagy dysfunction in bone cells is associated with the onset of bone diseases such as osteoporosis. This review had the purpose of discussing the issue to confirm whether a relationship between autophagy dysfunction and osteoporosis exits.